Text Summarization using Gravitational Search Algorithm - Mahmood Salman, Hayder (Opción, 2019)
Extractive summarization is the process of precisely selecting a set of sentenc- es from a corpus which can essentially be a demonstrative of the original corpus in a limited space. This paper presents a model which based on computing the coherence and the readability of each sentence in the corpus. The Gravitational Search Algorithm utilized to select the most suitable sentences to be included in the generated summary. The proposed model is evaluated using Doc. 2002 dataset The performance of the proposed model is evaluated using Rouge software. The calculated results support the success of the proposed model compared with other similar methods.